Force-length relationship modeling of wrist and finger flexor muscles - Hauraix, H.; Goislard, D. E.; Monsabert, B.; Herbaut, A.; Berton, E.; Vigouroux, L. (Medicine & Science in Sports & Exercise, 2018)
Introduction Because the hand joints possess a broad range of motion, the muscle length can vary importantly which might result in significant variations of the muscle force-generating capacities. However, facing the complexity of this musculoskeletal system, no study has examined the effect of hand muscle length change on muscle force. This study aimed to characterize the force-length relationship of muscles involved in wrist and metacarpophalangeal flexion.